THEORETICAL FOUNDATIONS OF CULTURE IN LANGUAGE EDUCATION - Tairova Ruzakhon Umidbek qizi (World Scientific Research Journal, 2025)
Annotation: The article Theoretical Foundations of Culture in Language Education explores the critical role that cultural understanding plays in the acquisition and teaching of languages. It examines various theoretical frameworks that underpin the integration of culture into language pedagogy, highlighting the interdependence between language and cultural identity. The article discusses how culture influences language use, communication styles, and learner motivation, stressing the need for culturally responsive teaching methods. It also reviews approaches that address intercultural competence as a core educational goal, promoting learners’ ability to navigate and respect diverse cultural contexts. By analyzing cognitive, sociolinguistic, and pragmatic perspectives, the article underscores that effective language education must extend beyond grammar and vocabulary to include cultural awareness. This comprehensive view supports the development of learners’ communicative competence in authentic social interactions. Ultimately, the article advocates for a balanced incorporation of culture and language instruction to foster deeper understanding and meaningful global communication.